2018
DOI: 10.1080/20550324.2018.1550924
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of cellulose nanofiber composites with nanodiamond as nanocarbon filler

Abstract: Cellulose nanofibers are green nanomaterials because of their biodegradability and sustainability, they are also attractive structural materials because of their high mechanical performance. For further expansion of their application and acquisition of their reliability, mechanical reinforcement and functionalization of cellulose nanofiber materials are required. In this work, we focused on the mechanical properties and thermal conductivities of composites of cellulose nanofibers and a nanodiamond (ND). Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…These results indicate that the ND content in the epoxy/ND composites can be controlled. In addition, in the XRD profiles of the epoxy/ND composites, the intensities of the diffraction peaks originating from the (111) plane of the NDs increased with an increase in ND content, as shown in Figure S5 in the Supporting Information. However, no diffraction peaks of the PVA crystallites were observed because the amounts of PVA in their composites were small.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…These results indicate that the ND content in the epoxy/ND composites can be controlled. In addition, in the XRD profiles of the epoxy/ND composites, the intensities of the diffraction peaks originating from the (111) plane of the NDs increased with an increase in ND content, as shown in Figure S5 in the Supporting Information. However, no diffraction peaks of the PVA crystallites were observed because the amounts of PVA in their composites were small.…”
Section: Resultsmentioning
confidence: 93%
“…In particular, nanocarbon materials such as CNTs and nanographene are promising thermally conductive materials. Further, our group has investigated the use of composites, including nanodiamonds (NDs), for reinforcements of mechanical properties and enhancement of thermal conductivity in previous reports and developed the ND nanocomposites. In particular, NDs are excellent electronic insulators having the diamond structure, making them suitable as TIMs in electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The phase images showed that a good dispersion of CNC nanofillers was employed and no large aggregation was observed. Another study on cellulose nanofibre (CNF)/nanodiamond as nanofiller composite was reported by Kato et al 15 It was revealed that nanodiamonds prepared via detonation technique showed a spherical shape with a diameter of 10 nm and they were well dispersed in water due to their hydrophilic oxygen surface functional groups, as shown in Figure 7. It was reported that the nanodiamonds can be used as a nanofiller for improved mechanical and thermal properties of bionanocomposites.…”
Section: Morphological Characterization Of Bionanocompositesmentioning
confidence: 95%
“…The BNNS has obvious diffraction peaks at 26.7 , 41.6 , 43.7 , 50.1 , and 55.0 , consistent with their crystal planes of (002), (100), (101), (102), and (004). 47,48 DN only has a characteristic diffraction peak corresponding to a diamond crystal face of (111) at 43.8 . 49 Because the diffraction peak of DN was close to that of BNNS, there is no obvious diffraction peak of DN in the complex filler due to the its low content.…”
Section: Morphology and Structure Analysis Of Fillers And Their Epoxy...mentioning
confidence: 99%